PENGARUH PEMBERIAN TERAPI MADU TERHADAP INTENSITAS NYERI PEMASANGAN INFUS PADA ANAK USIA PRA SEKOLAH - Putri Risza Gusrina; Husni Husni; Nehru Nugroho (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract: Pain is a subjective experience that is common in children who are difficult to accurately identify. One of the main sources of pain that is often performed in children is invasive medical procedures such as infusion. The use of the sweet solution technique is easier and can be done by nurses. The aim was to determine the effect of honey therapy on the intensity of pain in infusion in pre-school age children. The quasi-experimental method with the type of nonequivalent control group, post-test only design. Control groups were observed, and given to children without intervention, intervention groups were observed and intervened. Samples were taken using purposive sampling with 23 people in one group and all study samples were 46 people. The analysis used was non-parametric using the Mann-Whitney test. The results showed no influence or difference in preschool children in the intervention group given honey therapy and the control group that was not given honey therapy (P = 0.005). Sweet solution is a method or technique that can be used to reduce pain by diverting the attention of clients to overcome the problem of pain in children more easily and can be done by nurses.Keywords: Pain in children, non-pharmacological methods, honey therapy